PERSEPSI MASYARAKAT TERHADAP PERILAKU PACARAN MAHASISWA KOS DI RW VII KELURAHAN GUNUNG PANGILUN KECAMATAN PADANG UTARA KOTA PADANG - -, DESJULINA - (Pendidikan Sosiologi, 2014)
Now a day, along with the many of boarding students who lived in the RWVII at Gunung Pangilun village, hence it is not infrequently appear that there arealso behaviors that violate the values and norms in the society. One of theemergent behaviors of students boarding is the courtship behavior that violatenorms ang values. As for the question of this research is how the publicperception of the courtship behavior of boarding students in RW VII at GunungPangilun village, the north of the town Padang district, in Padang city. Thepurpose of this study is to describe the public perception of courtship behavior ofboarding students in RW VII at Gunung Pangilun village, the north of the townPadang district, in Padang city.The theory that used in this study is the phenomenological theory byAlfred Schutz. This research approach is qualitative by using the descriptiveresearch. The retrieval techniques infoemants were conducted by using purposivesampling. The types of data in this study are primary data and secondary data.Data were collected through interviews, observation and document studies byusing the unit of analysis is the group. The data analysis model that used isinteractive model according to Miles and Huberan.Based on the results of research that has been conducted on the publicperception of the courtship behavior of boarding students in RW VII at GunungPangilun village, it can be inferred, namely: a) the courtship behavior of theboarding student is seen as a behavior that has no shame, b) it is seen as abehavior that does not comply with the norm of society, c) it is seen as a behaviorthat is incompatible with the religion and culture, d) courtship behavior is seen asa behavior that can negatively inpact the community of environment, e) courtshipbehavior of the boarding students is seen as a behavior that is incompatible withhis status as a studentâs college, f) courtship behavior of the boarding students isseen as a behavior that makes the image of the institution/ college to be bad orcontaminated.